Lesões cervicais não cariosas são mais frequentes em pacientes com bruxismo do sono? - Miranda, Jean Soares [UNESP]; Barcellos, Aline Serrado de Pinho [UNESP]; Oliveira, Alloma de Souza; Paradella, Thaís Cachuté [UNESP]; Kimpara, Estevão Tomomitsu [UNESP]; Chaves, Maria das Graças Afonso Miranda (Editora Cubo, 2017)
Objective: to verify the frequency in non-carious lesions in patients with and without sleep bruxism and to try to list the occurrence of such lesions in patients with this parafunctional habit. Material and Methods: 67 patients ranging from 18 to 70 years of age, which all signed a free and consent form were evaluated. Patients with neurological diseases and/or partially or totally edentulous were excluded from the study. Bruxism diagnosis was performed using a validated questionnaire based on the combination of at least two positive confirmations of bruxism. Diagnosis of non-carious cervical lesions (NCCL) was performed by a single calibrated examiner, using #5 clinical probe, intraoral mirror and air flow, analyzing all surfaces of the teeth present in the mouth. The lesions were classified as abfraction, abrasion or erosion. Statistical analysis was performed by U Mann- Whitney test, at 5% level of significance. Results: sixty patients were diagnosed with bruxism (91.3%) and only seven patients (8.7%) did not present this parafuctional habit. Regardless the gender, five patients (10.1%) presented absence of lesions and 62 patients (89.9%) presented some NCCL. 70% presented abfraction, 41% abrasion and no patient presented erosion. Statistical analysis showed a p-value of 0.03, which demonstrated significant statistical difference of NCCL between the groups. Conclusion: a higher frequency of NCCL in patients with bruxism was observed when compared to patients without this parafuction.
Are non-carious cervical lesions more frequent in sleep bruxism patients?
Keywords: Abfraction; Bruxism; Non-carious cervical lesions